Dvigatel'nye reaktsii i svoistva vnimaniya v deistviyakh yunykh shpazhistov - Ivanov, I. P. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
On the importance of the examination and inclusion of psychological characteristics in training and competiotion in epee-fencing.